Penerapan Pendekatan Pembelajaran Berdiferensiasi dalam Model Problem Based Learning pada Pembelajaran Bahasa Arab (Lembaga Pengembangan Kinerja Dosen, 2025)
Arabic language instruction at the elementary school level often faces challenges due to low student engagement and the lack of teaching strategies that account for diverse learning characteristics. Conventional one-size-fits-all teaching models tend to overlook differences in students’ readiness, interests, and learning styles, which in turn leads to decreased motivation and poor academic outcomes. To address these issues, this study examines the implementation of a differentiated instruction approach within the Problem-Based Learning (PBL) model as a strategy to foster a more adaptive, participatory, and meaningful Arabic learning experience. The objective of this research is to describe the strategy for applying differentiated instruction within the PBL framework and to analyze its impact on student engagement and learning outcomes. This study employs a descriptive qualitative method, using observation, interviews, and documentation as data collection techniques. Informants in this research consist of one Arabic language teacher and three fifth-grade students from SDIT Asy-Syafi’i. The results indicate that the implementation of this approach positively influences students’ active participation, learning motivation, as well as communication and critical thinking skills in Arabic language learning. Differentiation strategies applied in the content, process, and product stages of PBL successfully accommodate student diversity and create a more inclusive learning experience.